2021
DOI: 10.7554/elife.64020
|View full text |Cite
|
Sign up to set email alerts
|

Coronary plaque composition influences biomechanical stress and predicts plaque rupture in a morpho-mechanic OCT analysis

Abstract: Plaque rupture occurs if stress within coronary lesions exceeds the protection exerted by the fibrous cap overlying the necrotic lipid core. However, very little is known about the biomechanical stress exerting this disrupting force. Employing optical coherence tomography (OCT), we generated plaque models and performed finite-element analysis to simulate stress distributions within the vessel wall in 10 ruptured and 10 non-ruptured lesions. In ruptured lesions, maximal stress within fibrous cap (peak cap stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Optical coherence tomography (OCT) provides detailed images of the fibrous cap using near infrared light delivered via a fiber optic wire. The images provided by OCT correlate well with histological features high signals in the fibrous cap signify macrophage adherence and thrombus formation [ 28 , 29 ]. Near infrared spectroscopy (NIRS) is another catheter-based invasive technique.…”
Section: Imaging Biomarkers Of Vulnerable Plaquesmentioning
confidence: 97%
“…Optical coherence tomography (OCT) provides detailed images of the fibrous cap using near infrared light delivered via a fiber optic wire. The images provided by OCT correlate well with histological features high signals in the fibrous cap signify macrophage adherence and thrombus formation [ 28 , 29 ]. Near infrared spectroscopy (NIRS) is another catheter-based invasive technique.…”
Section: Imaging Biomarkers Of Vulnerable Plaquesmentioning
confidence: 97%
“…2A ). The thickness of the fragile cap, which is widely accepted and recognized in clinical practice, is 65 µm ( 17 ). TCFA, in the context of OCT, is defined as a lipid-rich plaque with a thin fibrous cap (the thinnest part is ≤65 µm), and the lipid component in a plaque occupies ≥2 quadrants ( 17 ).…”
Section: Oct Evaluation Of Atherosclerotic Plaque-related Factorsmentioning
confidence: 99%
“…The thickness of the fragile cap, which is widely accepted and recognized in clinical practice, is 65 µm ( 17 ). TCFA, in the context of OCT, is defined as a lipid-rich plaque with a thin fibrous cap (the thinnest part is ≤65 µm), and the lipid component in a plaque occupies ≥2 quadrants ( 17 ). A previous study performed a histomorphological analysis of 295 coronary plaques (105 fibrous plaques, 88 TCFAs and 102 ruptured plaques) in patients who suffered sudden cardiac death.…”
Section: Oct Evaluation Of Atherosclerotic Plaque-related Factorsmentioning
confidence: 99%
“…Mechanical deformations in the present study are not large, because studies have shown that the maximum displacement is less than 10% of the original artery dimensions. Hence, the linear elastic assumption is appropriate for the artery wall [ 30 , 31 ]. Based on the previous studies [ 9 , 17 ], time steps of 0.001 s, 0.005 s, and 0.01 s were used.…”
Section: Boundary Conditions and Numerical Techniquesmentioning
confidence: 99%